An ontogogy-based approach to resilient recovery support for disaster victims in Vietnam - Nguyen Hong Duc; Chutiporn Anutariya; Huynh, Trung Luong; Mozumder, Chitrini; AITCV, Vietnam; AIT Scholarships (Pathum Thani, Thailand : Asian Institute of Technology, 2024)
The recovery stage post-disaster involves communities, individuals, and infrastructure aiming to restore normalcy. However, after a disaster, uncertainty prevails, which will leave individuals unsure about required criteria and available welfare resources. Concerns for recovering prompt people to seek information from various sources, but fragmented and scattered data leads to confusion and time-consuming. This lack of cohesion delays access to crucial support. To address this, a research study proposes an ontology-based approach for disaster victims, which will serve as a structured knowledge base for streamlined recovery guidance.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Data Science and Artificial Intelligence
Research Studies Project Report (M. Eng.) - Asian Institute of Technology, 2024
Keywords: Ontology; Disaster relief -- Vietnam